Intersectoral partnerships and competencies for mental health promotion: a Delphi-based qualitative study in Finland. (2nd July 2021) - Tamminen, Nina; Solin, Pia; Barry, Margaret M; Kannas, Lasse; Kettunen, Tarja
Summary: The importance of intersectoral collaboration and partnership working in mental health promotion, together with the requisite competencies for effective collaboration, is widely acknowledged. This Delphi-based qualitative study examined how intersectoral collaboration and partnership work are constructed and adopted in mental health promotion practice. Descriptive data from a Delphi panel of mental health promotion practitioners working in the health sector ( n  = 32) were used as a data source. Thematic analysis was used to analyze the data. Applying the theory of collaborative advantage, eight themes of collaboration advantage and the related competencies were identified: management structure, leadership, communication and language, common aims, working processes, resources, trust, and commitment and determination. The themes capture the competencies required to influence and work with others to improve the mental health and wellbeing of individuals and communities. The identified theme areas can be used to inform education and training and capacity building for professional practice in mental health promotion. Future research is needed to explore other possible collaborative advantage themes in mental health promotion practice and the competencies required to facilitate effective partnerships across sectors. Further investigations are also needed on the identified theme areas in order to develop and guide capacity building and training in mental health promotion.